2004
DOI: 10.1074/jbc.m404628200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Ablation of Plasma Membrane Ca2+-ATPase (PMCA) 1 and 4 Indicates a Major Housekeeping Function for PMCA1 and a Critical Role in Hyperactivated Sperm Motility and Male Fertility for PMCA4

Abstract: The relative importance of plasma membrane Ca 2؉ -ATPase (PMCA) 1 and PMCA4 was assessed in mice carrying null mutations in their genes (Atp2b1 and Atp2b4). Loss of both copies of the gene encoding PMCA1 caused embryolethality, whereas heterozygous mutants had no overt disease phenotype. Despite widespread and abundant expression of PMCA4, PMCA4 null (Pmca4 ؊/؊ ) mutants exhibited no embryolethality and appeared outwardly normal. Loss of PMCA4 impaired phasic contractions and caused apoptosis in portal vein sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
324
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 309 publications
(348 citation statements)
references
References 26 publications
17
324
0
7
Order By: Relevance
“…PMCA4 mRNA has been detected in endothelial and VSMCs of porcine aorta (Szewczyk et al, 2007), in VSMCs from mouse carotid artery , and was shown as the most prominent PMCA mRNA transcript in mouse whole aorta (Okunade et al, 2004). PMCA4 protein expression has been reported in a mouse VSMC line and in isolated murine aortic VSMCs .…”
Section: Expression Of Plasma Membrane Calcium Atpases In the Vasculamentioning
confidence: 95%
See 4 more Smart Citations
“…PMCA4 mRNA has been detected in endothelial and VSMCs of porcine aorta (Szewczyk et al, 2007), in VSMCs from mouse carotid artery , and was shown as the most prominent PMCA mRNA transcript in mouse whole aorta (Okunade et al, 2004). PMCA4 protein expression has been reported in a mouse VSMC line and in isolated murine aortic VSMCs .…”
Section: Expression Of Plasma Membrane Calcium Atpases In the Vasculamentioning
confidence: 95%
“…Studies to date suggest that PMCA4 may modulate bulk Ca 2+ homeostasis, nNOS signalling (Pande et al, 2006 and eNOS activity (Holton et al, 2010). It is noteworthy that recent studies investigating PMCA4 in the cell cycle have concluded that its role is related both to its activity and its scaffolding effects )-this has been demonstrated using two mouse models, one in which there is a complete lack of PMCA4 protein, whilst the other has a mutant, non-functioning PMCA4 (Okunade et al, 2004;Schuh et al, 2004). The availability of the PMCA4 knockout mouse affords the opportunity for investigation of the effects of PMCA4 ablation on BP and arterial contractility.…”
Section: Pharmacological Modulation Of Plasma Membrane Calcium Atpasementioning
confidence: 99%
See 3 more Smart Citations